2019
DOI: 10.1002/mus.26518
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin is expressed in smooth muscle and afferent nerve fibers in the rat urinary bladder

Abstract: Introduction With increasing life expectancy, comorbidities become overt in Duchenne muscular dystrophy (DMD). Although micturition problems are common, bladder function is poorly understood in DMD. We studied dystrophin expression and multiple isoform involvement in the bladder during maturation to gain insights into their roles in micturition. Methods Dystrophin distribution was evaluated in rat bladders by immunohistochemical colocalization with smooth muscle, interstitial, urothelial, and neuronal markers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
(102 reference statements)
1
13
0
Order By: Relevance
“…The detailed proteomic analysis of the interface between the stomach wall and the pancreas confirmed previous biochemical and cell biological studies that have shown the presence of both dystrophin 10,11 and dystrophinassociated proteins [18][19][20] in smooth muscle cells. Dystrophin exists in various tissue-specific isoforms with the largest proteoforms of apparent 427 kDa being mostly expressed in muscle cells and the nervous system.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The detailed proteomic analysis of the interface between the stomach wall and the pancreas confirmed previous biochemical and cell biological studies that have shown the presence of both dystrophin 10,11 and dystrophinassociated proteins [18][19][20] in smooth muscle cells. Dystrophin exists in various tissue-specific isoforms with the largest proteoforms of apparent 427 kDa being mostly expressed in muscle cells and the nervous system.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to the usually positive effects of immune cell infiltration during muscle repair mechanisms following an acute injury, the chronic inflammatory phenotype of dystrophin-deficient muscle fibres appears to be mostly detrimental. 9 Dystrophin was previously established to be present in all muscle cell types, 10 including smooth muscles, 11 and dystrophinopathies were shown to be associated with gastrointestinal dysfunction. 4,5,[12][13][14][15] Thus, to investigate whether the smooth muscle protein constituents of the gastrointestinal system are majorly affected by dystrophin deficiency, we carried out a mass spectrometry-based proteomic analysis of the established genetic mdx-4cv mouse model of Duchenne muscular dystrophy, which also displays considerable abnormalities in the gastrointestinal system.…”
mentioning
confidence: 99%
“…A recent study found that dystrophin is expressed in smooth muscle cells and afferent nerve fibers in rat urinary bladders, meaning that micturition problems in MD may have both a myogenic and neurogenic component. 2 A better understanding of the pathogenesis of urinary difficulties is needed in this population as myopathic involvement of the detrusor would be expected to decrease the strength of bladder contractions and cause a large capacity, flaccid bladder, which was not observed in either study. 16 Very limited data exist regarding urologic issues in those with SMA.…”
Section: Discussionmentioning
confidence: 82%
“…Dystrophin expression has even been found in some nerves, including afferent nerves of the bladder. 2 The 2 most common forms, Duchenne MD (DMD) and Becker MD (BMD) are caused by 2 different inherited defects in the DMD gene (Xp21.2) responsible for the production of dystrophin. 3 Women are carriers with variable penetrance and men are more severely affected.…”
Section: Resultsmentioning
confidence: 99%
“…It is however apparent that despite skeletal muscle weakness being a primary clinical sign, the impact of D/BMD on smooth muscle may contribute to the presentation of co-morbidities, particularly within the urinary tract [6]. In boys with DMD, there is a 50% prevalence of lower urinary tract symptoms (LUTS) [7], which could in part be linked to the expression of dystrophin within the smooth muscle of the bladder and upper urinary tract [8]. Ambiguity surrounding the reporting of LUTS (i.e.…”
Section: Introductionmentioning
confidence: 99%